Economic empowerment of remote traditional communities through access to women's services, youth, business and work - Urip Wahyudin; Joko Suryono (AMCA Journal of Community Development, 2024)
The National Program for the Empowerment of Remote Indigenous Communities, led by the Ministry of Social Affairs in Indonesia, focuses on improving the condition of life and well-being of residents native to the area isolated. This research aims to analyze potential problems and needs for the empowerment of public custom remote that focus on empowering women, access service youth, and access to services, businesses, and work. This type of research is qualitative descriptive research using approach studies case. Data collection techniques use studies documentation, observation, interviews, and discussion group focused. Data analysis techniques use analysis models such as the inductive interactive Miles and Huberman model. Access research results in service empowerment women require access development involving the integration of a gender perspective that requires a framework of solid institutions and laws.​ Access services to youth require a development program. Villages that involve youth in the field of social economics show​ positive things in various areas. Access services work requires the development of an excellent local environment through cultivating plant hard, plant food, livestock, and fisheries.